Comparison between exergy and energy analysis for biodiesel production. (1st March 2016) - Amelio, A.; Van de Voorde, T.; Creemers, C.; Degrève, J.; Darvishmanesh, S.; Luis, P.; Van der Bruggen, B.
Abstract: This study investigates the exergy concept for use in chemical engineering applications, and compares the energy and exergy methodology for the production process of biodiesel. A process for biodiesel production was suggested and simulated in view of the energy and exergy analysis. A method was developed to implement the exergy concept in Aspen Plus 7.3. A comparison between the energy and the exergy approach reveals that the concepts have similarities but also some differences. In the exergy study, the reaction section has the largest losses whereas in the energy study separation steps are the most important. An optimization, using both concepts, was carried out using the same parameters. The optimized results were different depending on the objective function. It was concluded that exergy analysis is crucial during the design or redesign step in order to investigate thermodynamic efficiencies in each part of the process. Highlights: New flowsheet for the production of biodiesel simulated with Aspen Plus. Calculation of the exergetic costs and several interesting indexes. Comparison of exergy and energy analysis for the process studied.